1980
DOI: 10.1159/000117746
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens in Tardive Dyskinesia in Male Psychiatric Patients

Abstract: The beneficial effect of estrogens on L-dopa-induced dyskinesias and on tardive dyskinesia has recently been reported. In this open pilot study, conjugated estrogens (CE) were administered to 20 male chronic psychiatric patients (age range: 29-63). All except 1 were still on neuroleptic medication and 8 of them were still receiving an antiparkinsonian agent. Patients were divided into 4 equal groups. Groups I and II (< 51 years old) received daily CE at different doses (1.25 or 2.50 mg) for a period of 6 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…It has been observed that women suffer more Parkinsonism, akathasia and tardive dyskinesia than men (1,12). Villeneuve et al (13) investigated the effect of oestradiol treatment on extrapyramidal symptoms in males and found a slight reduction in the intensity of dyskinetic movements, but the expected increase in Parkinsonism was not supported by their results. In their discussion they went on to report a single case of a menopausal woman suffering from tardive dyskinesia.…”
Section: Introductionmentioning
confidence: 94%
“…It has been observed that women suffer more Parkinsonism, akathasia and tardive dyskinesia than men (1,12). Villeneuve et al (13) investigated the effect of oestradiol treatment on extrapyramidal symptoms in males and found a slight reduction in the intensity of dyskinetic movements, but the expected increase in Parkinsonism was not supported by their results. In their discussion they went on to report a single case of a menopausal woman suffering from tardive dyskinesia.…”
Section: Introductionmentioning
confidence: 94%
“…In 1978, Villeneuve et al reported that 16 of 20 female patients with dyskinesias showed an improvement in the dyskinesias when treated with oestrogen 56 . A significant decrease in the intensity of neuroleptic‐induced dyskinesias in male psychiatric patients placed on conjugated equine oestrogen was also observed 57 . It has also been shown that administration of exogenous oestrogens affects the onset or severity of l ‐DOPA‐induced dyskinesias.…”
Section: Oestrogen and Clinical Studies Of Parkinson's Diseasementioning
confidence: 99%
“…After menopause, women require larger doses of neuroleptics and are more at risk to develop more and more severe forms of dyskinesias [41]. Some clinical studies in women with tardive dyskinesia have shown beneficial effects of estradiol [42][43][44][45] whereas other This review will survey the effects of estrogens on mental and neurodegenerative diseases. More specifically we will focus on schizophrenia, depression as well as AD and PD because of their high prevalence and the documented effects of steroids in these diseases.…”
Section: Introductionmentioning
confidence: 99%